ANALISIS UNIVARIAT DAN MULTIVARIAT CONTO SEDIMEN SUNGAI DALAM PENENTUAN POTENSI MINERALISASI LOGAM DI HALMAHERA BAGIAN TIMUR, PROVINSI MALUKU UTARA: UNIVARIATE AND MULTIVARIATE ANALYSIS OF STREAM SEDIMENT SAMPLE FOR DETERMINATION OF METAL MINERALIZATION POTENTIAL IN THE EASTERN PART OF HALMAHERA, NORTH MALUKU - Faisal, Reza Mochammad; Nugroho, Irfan Budiaji; Priadi, Bambang (Buletin Sumber Daya Geologi, 2020)
Geochemical research used the analysis method of -80 mesh of active stream sediment samples is one of the early phase exploration specially in finding out metallic mineral deposits. Easternpart of Halmahera with its complex geologic setting and a metallogenic region is being potential to form metallic deposits, which create some variation and interesting geochemical performances. The geochemistry of stream sediment data by means in the form of elements distribution maps represent the basic important information of mineralization indications, which enable for detail follow up research, specifically nickel mineralization associated with the Ultrabasa Complex lithology. Interpretation of geochemical data in the study area with univariate and multivariate statistical analysis approaches consisting of elements of Cu, Pb, Zn, Co, Ni, Mn, Ag, Fe, Cr, and Au, the process of enrichment of geochemical elements in the surface environment is shown by the spatial association of Co, Ni, Fe and Mn, namely the enrichment of elements due to chemical binding (scavenging) by Fe and Mn oxides. Based on the kindship of elements or relations between elements obtained two groups of elements, namely the bonding elements of Cu-Pb-Zn-Ag-Cr and Co-Ni-Mn-Fe-Au, but not all groups of element associations can be related to the lithology that develops in the study area.